Contribution of Bicarbonate Assimilation to Carbon Pool Dynamics in the Deep Mediterranean Sea and Cultivation of Actively Nitrifying and CO2-Fixing Bathypelagic Prokaryotic Consortia - La Cono, Violetta; Ruggeri, Gioachino; Azzaro, Maurizio; Crisafi, Francesca; Decembrini, Franco; Denaro, Renata; La Spada, Gina; Maimone, Giovanna; Monticelli, Luis S.; Smedile, Francesco; Giuliano, Laura; Yakimov, Michail M. (Frontiers in Microbiology, 2018)
Covering two-thirds of our planet, the global deep ocean plays a central role in supporting life on Earth. Among other processes, this biggest ecosystem buffers the rise of atmospheric CO2. Despite carbon sequestration in the deep ocean has been known for a long time, microbial activity in the meso- and bathypelagic realm via the ‘assimilation of bicarbonate in the dark’ (ABD) has only recently been described in more details. Based on recent findings, this process seems primarily the result of chemosynthetic and anaplerotic reactions driven by different groups of deep-sea prokaryoplankton. We quantified bicarbonate assimilation in relation to total prokaryotic abundance, prokaryotic heterotrophic production and respiration in the meso- and bathypelagic Mediterranean Sea. The measured ABD values, ranging from 133 to 370 µg C m-3 d-1, were among the highest ones reported worldwide for similar depths, likely due to the elevated temperature of the deep Mediterranean Sea (13-14°C also at abyssal depths). Integrated over the dark water column (≥ 200m depth), bicarbonate assimilation in the deep-sea ranged from 396 to 873 mg C m-2 d-1. This quantity of produced de novo organic carbon amounts to about 85-424% of the phytoplankton primary production and covers up to 62% of deep-sea prokaryotic total carbon demand. Hence, the ABD process in the meso- and bathypelagic Mediterranean Sea might substantially contribute to the inorganic and organic pool and significantly sustain the deep-sea microbial food web. To elucidate the ABD key-players, we established three actively nitrifying and CO2-fixing prokaryotic enrichments. Consortia were characterized by the co-occurrence of chemolithoautotrophic Thaumarchaeota and chemoheterotrophic proteobacteria. One of the enrichments, originated from Ionian bathypelagic waters (3000m depth) and supplemented with low concentrations of ammonia, was dominated by the Thaumarchaeota ‘low-ammonia-concentration’ deep-sea ecotype, an enigmatic and ecologically important group of organisms, uncultured until this study.